Mental Recovery Post Cianjur Earthquake Disaster Among Nursing Student Who Living in Cianjur - Galih Jatnika; Yuswandi; Achmad Setya Roswendi; Hikmat Rudyana; Musri; Chatarina Suryaningsih; Acep Hasan; Oyoh; Nunung Nurjanah; Muhammad Budi Santoso; Rini Mulyati; Juju Juhaeriah; Dewi Umu Kulsum; Ritha Melanie; Meivi Sesanelvira; Ismafiaty; Lina Safarina; Suharjiman; Fitri Anggraeni; Setiawati; Kiki Gustryanti (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
It is been almost 1 month since the Cianjur earthquake disaster, but there are still many problems that have not been resolved. One of these problems is the post-disaster trauma of the people affected by the Cianjur earthquake. Post-disaster mental recovery efforts are needed, especially for nursing students who are domiciled in the Cianjur region. The purpose of this community service activity is to carry out post-disaster recovery efforts and provide material support to nursing students who are domiciled throughout the Cianjur. This community service activity was held on December 19 2022 by all lecturers, educational staff, and nursing student association (HIMA) Fitkes Unjani by providing deep breathing relaxation therapy and material support assistance for 32 nursing students who live in 4 subdistricts in Cianjur. The results of the recovery effort showed that there was a difference in the average anxiety score between pre and postmental recovery therapy with a significant value of 0.001, (<0.05), which means that post-mental recovery therapy can significantly reduce anxiety scores. Deep breathing relaxation therapy has been proven to be able to significantly assist the mental recovery process after the Cianjur earthquake disaster for nursing students who live in Cianjur. It is suggested to all nursing students affected by the Cianjur earthquake to apply this therapy to further reduce anxiety after the Cianjur earthquake.